Is There any Effect of ESG Performance in the Improvement of Financial Risk in ASEAN-5? - Nadia Rahma; Rofikoh Rokhim (Research Collaboration Community (RCC), 2022)
Public awareness in social and environmental sustainability became a challenge that turned into general assessments. ESG (Environmental, Social, Governance) performance became essential. Hence, the firm that does not apply ESG criteria in its business activities will face a consequence from investors impacting its performance, associated with financial risk. This study examines ESG performance within ESG score, ESG controversy, and BGD (Board Gender Diversity) on the total and systematic risk as a proxy for the financial risk of public companies listed on the stock exchange. This study uses a sample of 105 listed public firms from each stock exchange in ASEAN-5 (Philippines, Indonesia, Malaysia, Singapore, and Thailand) from 2016 to 2020 and applies panel regression analysis. The result suggests that ESG Score significantly influences total but not systematic risk in ASEAN-5. ESG controversy does not considerably affect total and systematic risk. BGD significantly influences total risk but not systematic risk. The findings will help investors and portfolio managers evaluate how ESG performance influences the firm's financial risk and make better investment decisions in ASEAN-5.